(untitled) (Journal of Asian Development Studies, 2025)
The paper adopting political psychology lenses of “motivated reasoning,” and “discrediting strategies” looks to capture and dissect one of the worst vilification campaigns in Pakistan’s history, launched by a sitting government against its political opponents. The battleground turned out to be Federal Board of Revenue (FBR) and its Track and Trace System (TTS) – a technological solution capable of monitoring industrial production and loading units, tracking vehicles, and tracing specified products across the supply chain for tax purposes. After five failed attempts between 2008 to 2020, FBR ended up procuring a cutting-edge TTS in March 2021 with assistance from the World Bank and successfully rolling it out over the next year. However, after the regime change operation of April 9, 2022, Pakistan Democratic Alliance (PDM) government sought to exploit TTS’s procurement and implementation as a tool to launch and sustain a malicious vilification campaign against Pakistan Tehreek-e-Insaf (PTI) and its leadership. Four formal inquiries committees (ICs) were instituted, one after the other, which essentially held that, barring routine hiccups and delays, TTS’s procurement was fair, transparent, and robust. This sustained inquisition fuelled a phony media trial and a vicious discrediting campaign, which may or may not have harmed PTI as a political party, but it definitely harmed TTS itself – creating a spectre of throwing baby with bathwater. The paper incisively stocktakes FBR’s rendezvous with TTS, and an exegesis of the ICs and their reports and provides critical insights into the way statecraft is conducted in Pakistan, and by extension, in developing countries.